Решение научно-исследовательских задач с помощью настольного сканирующего электронного микроскопа Phenom ProX - Верцанова, Е.В. (Наука та інновації, 2014)
Phenom ProX — современный, быстрый, эффективный универсальный настольный сканирующий электронный
микроскоп с интегрированной системой энергодисперсионного анализа. Уникальная конструкция позволяет применять его для решения разнообразных научно-исследовательских вопросов, задач материаловедения, контроля
качества на производстве, криминалистики, фармацевтики и обучения специалистов. Phenom ProX — сучасний, швидкий, ефективний універсальний настільний скануючий електронний мікроскоп з інтегрованою системою енергодисперсійного аналізу. Унікальна конструкція дозволяє застосовувати його
для вирішення науково-дослідних проблем, задач матеріалознавства, контролю якості на виробництві, криміналістики, фармацевтики та навчання спеціалістів. Phenom ProX — morden effective universal desktop Scanning
Electron Microscope with integrated EDS system. Phenom-
World helps customers to stay competitive in a world where
critical dimensions are continuously getting smaller. All Phenom
desktop systems give direct access to the high resolution and
high-quality imaging and analysis required in a large variety of
applications. They are affordable, flexible and a fast tool enabling engineers, technicians, researchers and educational professionals to investigate micron and submicron structures.